CHARACTERISTICS OF TRYPSIN ISOLATED FROM THE INTERNAL ORGANS OF YELLOWFIN TUNA AND STABILITY IN NaCl: KARAKTERISTIK TRIPSIN YANG DIISOLASI DARI ORGAN DALAM IKAN TUNA SIRIP KUNING DAN STABILITASNYA DALAM NaCl - Tati Nurhayati; Asadatun Abdullah; Fakhrina Auliya; Raden Hilman Wirayudha; Riki Kurniawan (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2025)
The demand for enzymes in Indonesia is extremely high, and they are still imported from other countries. Commercial trypsin is usually extracted from the pancreas of pigs and cattle, so other alternative sources are needed from fish, namely the intestines, liver, and spleen of tuna. The intestine, liver, and spleen are internal fish organs that contain trypsin with different characteristics. This study aims to determine the characteristics of trypsin in the internal organs of yellowfin tuna and its stability in NaCl. The method used was a Completely Randomized Design with the treatment of different types of intestines, liver, and spleen of tuna. Optimum trypsin activity was at 60°C and pH 8, with a specific activity value in the intestine of 0.948±0.114 U/mg, liver of 0.610±0.029 U/mg, and spleen of 0.605±0.159 U/mg. The maximum reaction speeds (Vmax) showed the largest value for the intestine, liver, and spleen were 0.248 mmol/s, 0.138 mmol/s, and 0.096 mmol/s, respectively. The constant values (Km) obtained for the intestine, liver, and spleen were 2.342, 2.268, and 1.276 mM, respectively. Trypsin has a molecular weight range of 20–30 of approximately 28 kDa. The trypsins extracted from the intestine and liver were relatively stable in up to 30% NaCl with a minimum relative activity of 60%, whereas the trypsin extracted from the spleen was relatively stable up to 20% NaCl with 54% relative activity. Based on their activity and characteristics, the internal organs of tuna, especially the intestines and liver, have the potential to be sources of trypsin.